PENGUKURAN KEPUASAN PELANGGAN DENGAN SERVICE QUALITY DAN IMPORTANCE PERFORMANCE ANALYSIS (STUDI KASUS PADA LAYANAN PT. MRT JAKARTA) - Sella Ayu Lestari (2023)
Jakarta, as the center of government and business, faces the complexity of mobility triggered by population growth and traffic problems. To address these challenges, innovations have been made in the transportation sector, including the development of the MRT. The significant impact of the COVID-19 pandemic has influenced the mobility patterns of the public and the use of public transportation. Surveys indicate a drastic decrease in the use of public transportation, including MRT Jakarta, due to the pandemic. Although there is a recovery trend after three years of the pandemic, the number of customers has not reached pre-pandemic levels. The aim of this research is to measure customer satisfaction with the quality of services provided by PT. MRT Jakarta. Data collection was conducted through a questionnaire involving 97 MRT Jakarta customers. This study utilizes the Service Quality (SERVQUAL) method and Importance Performance Analysis (IPA). The results of the SERVQUAL method show an overall average gap value of -0.51, indicating that the services provided by PT. MRT Jakarta fall short of or even below customer expectations. The Importance Performance Analysis results identify attributes in Quadrant I as the top priority for improvement, with the highest gaps being cleanliness and comfort of toilets at -0.82 and the friendliness and courtesy of the staff at -0.80.